Destination Image of street food on China town an impact on tourists' dining experiences: - Poltanee, Issarapong; Thavornsil, Thanapol (CENTRAL ASIA AND THE CAUCASUS, 2022)
Destination Image is considered that is important for consumers, because consumers they choose vacation destinations based on their image, especially Yaowarat Road Thailand. The purpose of this research is to develop a model of image structure of street food on Yaowarat Road that affects the eating of Thai consumers in Bangkok which is a quantitative research. Data were collected with a sample of 420 people of consumers traveling to eat street food in Yaowarat District, Bangkok. Analysis of the structural equation model revealed that consistent with empirical information by the chi-square value is equal to 1.022, the level of conformity index is equal to 0.915, the comparative fit index is equal to 0.976, the root index of the squared means of the error estimation is equal to 0.049 which has a harmonious with empirical data. The results of the hypothesis test that analyzes the causal influence between the latent variables within the experience, satisfaction, willingness to return to travel and intention of word of mouth. For the external variables, the image of a tourist attraction has a statistically significant direct influence at level 0.001, it can be said that to promote the image of Yaowarat street food needs to be focused on creating an image through creating experiences and if having a good image will affect the satisfaction that will lead to the intention of traveling back and the word of mouth by the tourist in the end.